Internet of vehicles - safe and intelligent mobility : second International Conference, IOV 2015, Chengdu, China, December 19-21, 2015, proceedings /: second International Conference, IOV 2015, Chengdu, China, December 19-21, 2015, proceedings. (2015) - Unknown
No abstract available